Beyond Productivity: The Role of Organizational Support and Work Engagement in Employee Well-Being within the Automotive Industry - Layarda, Rhicard Geovadri; Handayani Harahap, Dewi; Lekahena, Femmy (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The automotive industry is a dynamic and complex manufacturing sector that requires employees not only to excel in technical skills but also to maintain psychological well-being in order to support optimal performance. Employee well-being is a crucial aspect that encompasses physical health, mental health, and job satisfaction. However, in practice, employee well-being is often influenced by psychosocial factors such as organizational support and work engagement. This study aims to analyze the influence of perceived organizational support and work engagement on employee well-being in the context of the automotive industry. The research involved 57 employees of PT. X selected through random sampling. The instruments used included the Employee Well-Being Scale (EWBS), the Perceived Organizational Support Scale (SPOS), and the Utrecht Work Engagement Scale (UWES). Data analysis was conducted using multiple linear regression. The results revealed that perceived organizational support and work engagement significantly influenced employee well-being (R² = 0.567; p < 0.05). Partially, perceived organizational support (β = 1.017; p = 0.015) and work engagement (β = 0.640; p = 0.000) contributed positively and significantly to employee well-being. These findings highlight the importance of organizational support and work engagement in enhancing employee well-being. The implications suggest that organizations need to strengthen internal support and design effective engagement strategies to promote a healthier and more productive workforce.Industri otomotif merupakan sektor manufaktur yang dinamis dan kompleks, yang menuntut karyawan tidak hanya unggul dalam keterampilan teknis, tetapi juga memiliki kesejahteraan psikologis yang baik guna mendukung kinerja optimal. Employee well-being menjadi aspek penting yang mencakup kesehatan fisik, mental, serta kepuasan kerja. Namun, dalam praktiknya kesejahteraan karyawan kerap dipengaruhi oleh faktor psikososial, seperti dukungan organisasi dan keterikatan kerja. Penelitian ini bertujuan untuk menganalisis pengaruh perceived organizational support dan work engagement terhadap kesejahteraan karyawan dalam konteks industri otomotif. Penelitian dilakukan pada 57 karyawan PT. X dengan metode random sampling. Instrumen yang digunakan meliputi Employee Well-Being Scale (EWBS), Perceived Organizational Support Scale (SPOS), dan Utrecht Work Engagement Scale (UWES). Analisis data menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa perceived organizational support dan work engagement berpengaruh signifikan terhadap employee well-being (R² = 0,567; p < 0,05). Secara parsial, perceived organizational support (β = 1,017; p = 0,015) dan work engagement (β = 0,640; p = 0,000) memberikan kontribusi positif dan signifikan terhadap kesejahteraan karyawan. Temuan ini menegaskan pentingnya dukungan organisasi dan keterikatan kerja dalam meningkatkan kesejahteraan karyawan. Implikasi penelitian menunjukkan perlunya organisasi untuk memperkuat dukungan internal serta merancang strategi keterlibatan kerja yang efektif guna mewujudkan tenaga kerja yang lebih sehat dan produktif.